Sekularisasi, Kultur Digital dan Geliat Agama: Tantangan dan Sketsa Berteologi Digital di Indonesia - Bobby Daniel Nalle (IAKN Ambon, 2021)
Secularization and digital culture are the influencing aspects that define the characteristics of religious societies in the 21st century. As a formation of the history of social change, these two elements greatly determine the efforts of religion, in doing theology and church services at the present, in the term of digital theology. Indeed, It is determined by the surprising rise of the COVID-19 pandemic which forces religious efforts to deal with digital things. As a new experience, digital theology seeks a form as to how the social change made it. Elements such as secularization, digital culture, and church formation become the important aspects to determine the direction of doing theology. Based on these new experiences, this paper will describe a sketch of how to doing digital theology in Indonesia, especially in the case of GMIT. With the theology of incarnation as the frame, digital theology puts the relational substance (God-human, among human relationships and between the real and digital world. As the digital world as a locus, digital theology therefore over a liquid digital church and the presensia-accompaniment model of a church mission to be the sketch of doing theology in the digital context in Indonesia.AbstrakSekularisasi dan kultur digital adalah dua elemen yang berpengaruh dalam ciri keberagamaan masyarakat religius di abad ke 21. Sebagai bentukan dari sejarah perubahan sosial, kedua hal ini sangat menentukan upaya beragama, berteologi dan bergereja dalam konteks kekinian. Salah satu istilah yang dikedepankan adalah teologi digital. Bentuk berteologi digital saat ini justru didorong oleh situasi pandemi COVID-19. Sebagai sebuah pengalaman dadakan dan baru berteologi secara digital menjadi upaya mencari bentuk mengikuti perubahan sosial` Elemen seperti sekularisasi dan kultur digital dan geliat beragama menjadi aspek yang menentukan arah berteologi. Dengan berpatokan pada pengalaman baru inilah tulisan ini berkenan memberikan gambaran sketsa berteologi digital di Indonesia melalui pengalaman bergereja di GMIT. Payung teologi inkarnasi yang dipakai sebagai usulan berteologi, mendasari keterkaitan relasional baik antara Allah dan manusia, antar-manusia maupun antara dunia real dan digital. Dalam memaknai ruang digital menjadi locus berteologi, maka sketsa gereja cair digital, dan model kehadiran digital presensia dan accompaniment menjadi sebuah tawaran bergereja dan bermisi dalam konteks digital di Indonesia.